Time-barred Periods in the Project of the First Book of the Civil Code - Kukuryk, Piotr (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2017)
Contrary to limitation periods, the Civil Code lacks de lege lata general principles governing time-barred periods. Their fragmentary regulation usually comes down to the determination of the so-called essentialia of a given time-barred period, namely its duration and the beginning of its run. The lack of a general code regulation is the source of numerous controversies. Therefore, in the doctrine, there has been a long-standing postulate to regulate selected aspects of the time-barred periods within the general part. This demand materialised only in the drafting of the First Book of the Civil Code, announced in October 2008, which regulates in the VII title, successively in two separate chapters, the issues of limitation periods (chapter I, Art. 181–191), and the time-barred period (chapter II, Art. 192–195). This article presents a concise analysis of these regulations. In particular, an attempt has been made to answer the question of to what extent their possible adoption will help to eliminate existing doubts. In conclusion, a positive assessment of the proposed legislation has been made. This is partly due to the fact that, in principle, the legislation reflects the established views of the doctrine and jurisprudence on the nature of time-barred periods.